- #1
Curious6
- 184
- 0
Hey, I really would appreciate some help with this one as I'm stuck on my coursework. It'll probably be easy for most of you but I forgot how to do this operation with logarithms. See this equation:
lny = lnx + BlnK + (1 - B)lnL.
How can I change that to one that removes the natural logarithms by means of using x = e^lnx? Thanks in advance!
lny = lnx + BlnK + (1 - B)lnL.
How can I change that to one that removes the natural logarithms by means of using x = e^lnx? Thanks in advance!